2018
DOI: 10.1096/fj.201801057r
|View full text |Cite
|
Sign up to set email alerts
|

Reduced myocyte complex N‐glycosylation causes dilated cardiomyopathy

Abstract: Protein glycosylation is an essential posttranslational modification that affects a myriad of physiologic processes. Humans with genetic defects in glycosylation, which result in truncated glycans, often present with significant cardiac deficits. Acquired heart diseases and their associated risk factors were also linked to aberrant glycosylation, highlighting its importance in human cardiac disease. In both cases, the link between causation and corollary remains enigmatic. The glycosyltransferase gene, mannosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 73 publications
1
6
0
Order By: Relevance
“…Together with our data that Neu5Ac/Gc-Gal-GlcNAc decreases in 22month-old mice and our MS data showing a reduction of complex-type glycans carrying terminal neuraminic acid, this suggests that sialylation might be critical for heart function. Notably, the reduction of complex-type N-glycans in our MS analysis of aged murine hearts corresponds with findings for mannosyl (α-1,3-)-glycoprotein β-1,2-N-acetylglucosaminyltransferase (Mgat1) KO mice, which develop dilated cardiomyopathy (Ednie et al, 2019).…”
Section: Discussionsupporting
confidence: 82%
“…Together with our data that Neu5Ac/Gc-Gal-GlcNAc decreases in 22month-old mice and our MS data showing a reduction of complex-type glycans carrying terminal neuraminic acid, this suggests that sialylation might be critical for heart function. Notably, the reduction of complex-type N-glycans in our MS analysis of aged murine hearts corresponds with findings for mannosyl (α-1,3-)-glycoprotein β-1,2-N-acetylglucosaminyltransferase (Mgat1) KO mice, which develop dilated cardiomyopathy (Ednie et al, 2019).…”
Section: Discussionsupporting
confidence: 82%
“…HCM has been reported in PMM2‐CDG, ATP6V1A‐CDG, and ATP6V1E1‐CDG . Recent studies have shown that abnormal glycosylation, for example, abnormal sialylation or reduced hybrid/complex N‐glycosylation, is related to heart disease . However, future investigations are required to understand the clinical relevance of these findings.…”
Section: Discussionmentioning
confidence: 99%
“…19 Recent studies have shown that abnormal glycosylation, for example, abnormal sialylation or reduced hybrid/complex N-glycosylation, is related to heart disease. [19][20][21] However, future investigations are required to understand the clinical relevance of these findings. So far, DCM has been described in FKRP-CDG, FKTN-CDG, POMT1-CDG, POMT2-CDG, DOLK-CDG, DPM3-CDG, and PGM1-CDG.…”
Section: Discussionmentioning
confidence: 99%
“…(Deng et al, 2016). Knockouts of other genes related to protein glycosylation have also been shown to alter ion signaling in cardiomyocytes (Ednie et al, 2019;Montpetit et al, 2009), resulting in cardiac abnormalities. Finally, a congenital genetic defect in Neu5Ac synthesis led to dilated cardiomyopathy, which was confirmed in a genetic knockout in zebrafish (Wen et al, 2018).…”
Section: Cell Reportsmentioning
confidence: 99%